2017
DOI: 10.1097/md.0000000000007886
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of idiopathic restrictive cardiomyopathy

Abstract: Idiopathic restrictive cardiomyopathy (RCMP) has not been fully understood because this disease is difficult to diagnose. The present study aimed to assess the clinical profile and outcome of idiopathic RCMP from a multicenter cohort.This investigation is a retrospective study of consecutive patients with idiopathic RCMP at 10 centers in Korea between 1990 and 2010. We evaluated the clinical characteristics of the patients and prognostic factors associated with mortality using multivariate Cox proportional haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…All-cause mortality for the overall cohort was 56%. The poor prognosis was consistent with a previous multicenter Korean study, where five-year overall survival was 64% [5].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…All-cause mortality for the overall cohort was 56%. The poor prognosis was consistent with a previous multicenter Korean study, where five-year overall survival was 64% [5].…”
supporting
confidence: 91%
“…On the other hand, only a few management recommendations were suggested, highlighting the lack of data on RCM. Indeed, except for TTR-CA, a few studies focused on RCM in recent years [4][5][6][7].…”
mentioning
confidence: 99%
“…Moreover, our study showed a five-year survival rate of 74.1% in LVNC patients, compared with the rate of 80–91% reported by Ce Wang et al and 52% reported by William Y Shi et al [ 14 , 20 ]. For RCM patients, the five-year survival rate of 51.1% was still lower than the rate of 64.6% in adult population, suggesting that patients who are diagnosed with RCM in childhood may have a worse prognosis than those diagnosed later in life [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following prognostic factors have been described in non-amyloid RCM (na-RCM): male sex, age >70 years, the New York Heart Association Functional Classification (NYHA class) ≥III, left atrial (LA) diameter >60 mm, and low cardiac output [8]. Recent studies underline the role of left ventricular end-diastolic diameter (LVEDD) and tricuspid regurgitation [9]. GDF-15 is considered a cardioprotective hormone due to its antioxidative, anti-inflammatory, and antiapoptotic properties [10].…”
Section: Introductionmentioning
confidence: 99%